2013
DOI: 10.5194/bg-10-6053-2013
|View full text |Cite
|
Sign up to set email alerts
|

The calcareous nannofossil <i>Prinsiosphaera</i> achieved rock-forming abundances in the latest Triassic of western Tethys: consequences for the <i>δ</i><sup>13</sup>C of bulk carbonate

Abstract: Abstract. The onset of pelagic biomineralization was a milestone in the history of the long-term inorganic carbon cycle: as soon as calcareous nannofossils became major limestone producers, the pH and supersaturation state of the global ocean were stabilized (the so-called mid-Mesozoic revolution). But although it is known that calcareous nannofossils were abundant already by the end of the Triassic, no estimates exist on their contribution to hemipelagic carbonate sedimentation. With this work, we estimate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Relatively few δ 13 C org records are available for the Rhaetian (ca. 205.7-201.3 ± 0.2 Ma;Williford et al, 2007;Schoene et al, 2010;Wotzlaw et al, 2014;Maron et al, 2015;Rigo et al, 2016), a stage marked by significant faunal turnovers in both the marine and continental realms, including taxa such as ammonites (Guex et al, 2004;Whiteside and Ward, 2011), conodonts (Kozur and Mock, 1991;Giordano et al, 2010;Karádi et al, 2019), bivalves , radiolarians (Carter, 1993;Ward et al, 2001;Carter and Hori, 2005;O'Dogherty et al, 2010), the coral reef community (Flügel and Kiessling, 2002), dinoflagellates and foraminiferans (Hesselbo et al, 2002), calcareous nannofossils (van de Schootbrugge et al, 2007;Preto et al, 2012Preto et al, , 2013, theropod dinosaurs (Olsen et al, 2002), and terrestrial plants (McElwain et al, 1999(McElwain et al, , 2009Kürschner et al, 2007;Bonis et al, 2009;Cesar and Grice, 2019). The Rhaetian experienced a series of biotic crises and turnovers that culminated in the crisis at the Triassic/Jurassic boundary (TJB), which supports the hypothesis of a step-like extinction pattern for the end-Triassic mass extinction (e.g., Hallam, 2002;Tanner et al, 2004;Whiteside and Ward, 2011;Lucas and Tanner, 2018;Karádi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few δ 13 C org records are available for the Rhaetian (ca. 205.7-201.3 ± 0.2 Ma;Williford et al, 2007;Schoene et al, 2010;Wotzlaw et al, 2014;Maron et al, 2015;Rigo et al, 2016), a stage marked by significant faunal turnovers in both the marine and continental realms, including taxa such as ammonites (Guex et al, 2004;Whiteside and Ward, 2011), conodonts (Kozur and Mock, 1991;Giordano et al, 2010;Karádi et al, 2019), bivalves , radiolarians (Carter, 1993;Ward et al, 2001;Carter and Hori, 2005;O'Dogherty et al, 2010), the coral reef community (Flügel and Kiessling, 2002), dinoflagellates and foraminiferans (Hesselbo et al, 2002), calcareous nannofossils (van de Schootbrugge et al, 2007;Preto et al, 2012Preto et al, , 2013, theropod dinosaurs (Olsen et al, 2002), and terrestrial plants (McElwain et al, 1999(McElwain et al, , 2009Kürschner et al, 2007;Bonis et al, 2009;Cesar and Grice, 2019). The Rhaetian experienced a series of biotic crises and turnovers that culminated in the crisis at the Triassic/Jurassic boundary (TJB), which supports the hypothesis of a step-like extinction pattern for the end-Triassic mass extinction (e.g., Hallam, 2002;Tanner et al, 2004;Whiteside and Ward, 2011;Lucas and Tanner, 2018;Karádi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…triassica reached up to 60% of the total rock mass (Preto et al., 2013). However, in the Southern Apennines (Pignola‐Abriola, Lagonegro Basin, Italy) and in the NCA (Hallstatt Basin, Austria) its abundance remained around 20% (Figure 5) (Demangel, 2022; Demangel et al., 2020; Preto et al., 2013). Late Triassic calcareous nannofossils are only reported from the Neo‐Tethys Ocean both in the Western and Southern parts and no evidence was documented in the central part of this ocean, that is, Turkey and Oman (personal observations of I. Demangel).…”
Section: Discussionmentioning
confidence: 99%
“…Calcareous nannofossils emerged in the Late Triassic; it was suggested that they reached rock‐forming abundance in peri‐platform palaeo‐environmental settings in the latest Triassic (Preto et al., 2013). A relatively rapid increase in calcite precipitation and carbon burial due to the increase of calcareous nannofossil abundance over aragonitic fossils could result in smaller fractionation of the carbonate flux and therefore a transient positive δ 44/40 Ca carb excursion if affecting the global fractionation factor (Blättler et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We find evidence that high temperature episodes were bottlenecks for complex life and cooling following higher temperature fluctuations allowed for origination and diversification. Permo-Triassic: (164,(167)(168)(169)(170)(171)(172)(173)(174)(175)(176)(177) Triassic-Jurassic: (178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190) Cretaceous: (191)(192)(193)(194)(195) Cenozoic: (196)(197)(198)(199) Fossils: (5,6,16) with only tropical/subtropical used ∆ 47 compilation Carbonate ∆ 47 data was compiled from (12)(13)(14)19,20,34,35) and references therein. Results in (19) were screened to remove all Arctic and Antarctic carbonates and all Cretaceous Interior Seaway carbonates to provide the best ...…”
Section: Time-dependent Variability Across Materialsmentioning
confidence: 99%